Patient‐reported functional and quality‐of‐life outcomes after transanal total mesorectal excision. Issue 4 (4th February 2019) - Keller, D. S.; Reali, C.; Spinelli, A.; Penna, M.; Di Candido, F.; Cunningham, C.; Hompes, R.
Abstract : Follow‐up of more than 1 year after transanal total mesorectal excision for rectal cancer demonstrated improved quality of life and stable or improved functional outcomes. Continued experience and operative efficiency hold promise for improved overall outcomes with this emerging technology. Key patient‐reported outcomes